Multidisciplinary Approach in the Rehabilitation of Complicated Crown-root Fracture: A Case Report - Acharya, Nisha; Samant, Praveen Singh; Gautam, Vanita; Singh, Ourvind; Halwai, Hemanta (Orthodontic Journal of Nepal, 2014)
The management of patients with traumatic injuries to their dentition poses a serious challenge in everyday general dental practice. For the rehabilitation of the complicated subgingival crown fracture of anterior teeth, multidisciplinary approach is often indicated. A combination of endodontic, orthodontic, periodontal and prosthodontic approach may be required. Orthodontic or periodontal intervention becomes an integral part for the exposure of the sound tooth structure of fractured anterior teeth with fracture line extending subgingivally. The aim of this paper is to discuss the immediate endodontic management followed by orthodontic extrusion of traumatized upper anterior teeth with fracture at the subgingival level. In order to expose the sound tooth structure for prosthodonticintervention, orthodontic extrusion was performed after endodontic treatment. To avoid extraction of the involved teeth, the multidisciplinary approach was adopted and finally the teeth were restored prosthodontically. The final result was esthetically pleasant and periodontically sound.